THE USE OF SENTINEL-2 IMAGERY FOR TOTAL SUSPENDED SOLIDS (TSS) ESTIMATION IN PORONG RIVER, SIDOARJO - Bioresita, Filsa; Firdaus, Hana Sugiastu; Pribadi, Cherie Bhekti; Hariyanto, Teguh; Puissant, Anne (Elipsoida : Jurnal Geodesi dan Geomatika, 2018)
ABSTRACT Sidoarjo mud disaster is an occurrence of hot mud bursts at drilling location of Lapindo Brantas Inc., Sidoarjo, Indonesia since 29th May 2006. In order to overcome the continuous mud flow, Indonesian government built embankment around the center of the mudflow. They also throw mud materials into the Porong River. The large and continuous disposal of mud material leads to sedimentation in Porong River. Remote sensing method with satellite imagery can be a solution to find out how much sedimentation occurred in Porong River as a result of mud’s disposal. Total Suspended Solid (TSS) calculation from satellite image can be indicator of sedimentation distribution.In previous studies, TSS distribution has been observed from Landsat-7 and Landsat 8 data. Nowadays, with ability of Sentinel-2 which has higher spatial resolution (10 m) and higher revisit time (up to 6 days), optimization of TSS distribution in Porong river can be done. Thus the objective of this research is analysis of Sentinel-2 imagery application to estimate TSS in Porong River. Result showed good correlation between in-situ data and TSS estimation from Sentinel-2 with value 0.72. Keywords : Sentinel-2, TSS, Porong River.